Polylogues on the mental lexicon an exploration of fundamental issues and directions - Libben, Gary; Jarema, Gonia; Kuperman, Victor, (Professor of linguistics) (John Benjamins Publishing Company, 2021)
"From its beginnings, the study of the mental lexicon has been at the crossroads of research and scholarship. This volume presents a polylogue--a textual conversation of many voices. It is designed to capture the excitement within the field and generate a deeper understanding of key issues and debates for established researchers, students, and readers interested in language and cognition. The first chapter examines how the mental lexicon itself can be seen as a polylogue. In the following six chapters, authors tackle the fundamental questions concerning future research on lexical representation and processing in an interactive structure that presents new perspectives and captures the excitement of the field. The themes include the value of cross-linguistic megastudies, the nature of meaning, how to capture truly natural language, what can be learned from lexical acquisition, the advantages of a functionalist perspective, and the role of schemas in understanding morphology and the lexicon"--